Efeitos da alteração dos níveis de ansiedade no desempenho de ratos em uma tarefa de discriminação apetitiva - Godinho, Monique Raquel Costa (2008)
The plus-maze discriminative avoidance paradigm has been used to study the relationship between aversive memory and anxiety. The present study aims to verify if the elevated plus-maze can provide information about appetitive memory and anxiety, through a task motivated by food reward. Animals were allowed to explore an elevated plus-maze and received reinforcement in one of the enclosed arms. In a test session performed 24h later, in the absence of reward, rats showed preference for the previously rewarded enclosed arm over the neutral enclosed arm. The administration of diazepam and pentylenetetrazole before training induced, respectively, anxiolytic and anxiogenic effects (as evaluated by open-arm exploration). Both drugs induced amnestic effects, i.e., lack of preference for the rewarded arm in the test session. The results suggest that appetitive memory can be influenced by anxiety levels as well. The plus-maze appetitive discrimination task seems to be a useful model to investigate the relationship between memory and anxiety